Blood pressure and 10-year cardiovascular risk profile of young hypertensives in Malaysia; a single centre study - Abdullah, Aszrin; Mohd Shah, Azarisman Shah; Abdul Razak, Tariq; Mohd Noor, Noriah (2010)
: Introduction: Hypertension is being identified in younger population and the need for earlier diagnosis and intervention has resulted in the introduction of prehypertension in the classification of hypertension. Hypertension prevalence is at 33% and they contribute to a rising incidence of cardiovascular disease. The objective of the study is to assesses the 10-year cardiovascular risk profile of young hypertensieves from a single centre in Malaysia. Methodology: A total of 484 subjects were screened at a primary health care clinic in Kuantan, Malaysia. 57 subjected between the ages of 20 and 40 with systolic and diastolic blood pressure ranges of between 120-159 mmHg and 80-99 mmHg respectively were enrolled into a cross-sectional observational study. The cardiovascular risk-factor profile was assessed and the 10-year cardiovascular risk determined. Results: The mean age of the subjects were 32.74 ± 5.78 years. The mean systolic arterial pressures were 132.38 ± 10.34, 87.17 ± 7.55 and 102.06 ± 7.37 mmHg respectively. The mean fasting blood sugar 4.67 ± 0.75 mmol/L, total cholesterol 5.82 ± 0.96 mmol/L , low-density lipoprotein 3.73 ± 0.86 mmol/L, high-density lipoprotein 1.40 ± 0.37 mmol/L and body mass index 28.72 ± 5.24 kg/m2. The mean cardiovascular risk point was 4.07 ± 5.35 wherein 91.23% were in the low 10-year Coronary Artery Disease risk category ( Framingham CV Risk Score ) Conclusion: A great majority of young subjects within the prehypertension and stage 1 hypertension range had a low 10-year Coronary Artery Disease risk. They did however show higher than normal total cholesterol, low-density lipoprotein and body mass index levels.